RISK FACTOR ANALYSIS OF MEASLES IN TODDLER - Yudied Agung Mirasa (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Background : Measles is a disease caused by a paramyxovirus that can cause complications and even death. Indonesia has the highest number of measles cases among other countries in Southeast Asia. Purpose : This study aimed to identify the major risk factors for measles in toddlers in Indonesia and the results of this analysis will be used as analytical data affecting Surabaya measles. Methods : This study method is a article review that examined a large number of scientific articles on childhood measles in Indonesia from 2015 to 2022. Pearsons correlation test is used to test the relationship between the results of an article review and the incidence of measles in Surabaya in 2022. Results : From the various articles reviewed above the variable of immune status is a variable of significant value in many articles. The correlation test between basic MR immunization and measles incidence in Surabaya in 2022 is of significant value. Conclusion : Immunization status is very important for measles prevention. All regions in Indonesia, especially the city of Surabaya, should be more intensive in improving immunization services for toddlers with measles to 100% coverage.Keywords: Article Review, Measles, Risk Factor, Surabaya, Toddler